2013
DOI: 10.2340/16501977-1114
|View full text |Cite
|
Sign up to set email alerts
|

Functional effects of robotic-assisted locomotor treadmill thearapy in children with cerebral palsy

Abstract: There are several limitations to this study, therefore these results should be regarded as preliminary. Further research consistent with the above indications is needed to investigate the impact of this new treatment option in patients with cerebral palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
119
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 29 publications
5
119
1
3
Order By: Relevance
“…The one using the Gait Trainer GT 1 (Reha Stim, Berlin, Germany) showed better improvements in the robot-assisted group compared with the control group treated with conventional physiotherapy only 18 while the other study using the Lokomat (Hocoma, Volketswil, Switzerland) found no differences between the groups. 19 However, both and especially the latter study comprised some deciding limitations.…”
Section: Introduction: a Summary Of Pertinent Researchmentioning
confidence: 98%
“…The one using the Gait Trainer GT 1 (Reha Stim, Berlin, Germany) showed better improvements in the robot-assisted group compared with the control group treated with conventional physiotherapy only 18 while the other study using the Lokomat (Hocoma, Volketswil, Switzerland) found no differences between the groups. 19 However, both and especially the latter study comprised some deciding limitations.…”
Section: Introduction: a Summary Of Pertinent Researchmentioning
confidence: 98%
“…It would appear that based on review of between group differences, effect size, PEDRO score and MCID, gait training without body weight support (pedometer based over-ground training, treadmill training without body weight support, and an instrumented feedback treadmill training) 19,20,32 was more effective than gait training with body weight support. 18,21,30,31,33 Gait training with body weight support effect sizes (-0.17 to .82) were lower than gait training without body weight support (1.32 to 3.20). However, 2 of the 3 studies that trained without body weight support enrolled only children with hemiplegia.…”
Section: Gait Trainingmentioning
confidence: 92%
“…[18][19][20][21][30][31][32][33] Scores on the PEDro for the articles in this category ranged from 4 to 8, with an overall average rating of 6.5 and median of 7. Of the 8 studies included in this category, 5 (62%) rated good 18-20, 30, 32 and 3 (38%) rated fair.…”
Section: Gait Trainingmentioning
confidence: 99%
See 2 more Smart Citations